2-Indolinone a versatile scaffold for treatment of cancer: a patent review (2008–2014). (1st February 2016) - Leoni, Alberto; Locatelli, Alessandra; Morigi, Rita; Rambaldi, Mirella
ABSTRACT: Introduction : 2-Indolinone is a well-known aromatic heterocyclic organic compound. A lot of work has been done on this bicyclic structure by academic and company researchers to synthesize compounds directed to a plethora of molecular targets in order to discover new drug leads. This review presents up-to-date information in the field of cancer therapy research based on this small building block. Areas covered : The present review gives an account of the recent patent literature (2008–2014) describing the discovery of 2-indolinone derivatives with selected therapeutic activities. In this period, a large amount of patents were published on this topic. We have limited the analysis to 37 patents on 2-indolinone derivatives having potential clinical application as chemotherapeutic agents. In this review, the therapeutic applications of 2-indolinone derivatives for the treatment of cancer reported in international patents have been discussed. Expert opinion : 2-Indolinone is the scaffold of the compounds considered from a medicinal chemistry perspective. Many of them have been developed and marketed for therapeutic use. In cancer chemotherapy, progress has been made in designing selective 2-indolinone derivatives. Some of them show preclinical efficacy. However, 2-indolinone has not exhausted all of its potential in the development of new compounds for clinical applications and remains a great tool for future research.